Mapping the Way through Court Procedures in Bulgaria - World Bank (Washington, DC, 2015)
The aim of this report is to illustrate the steps court users take in order to protect their interests through procedures carried out by courts. The focus is on the difference between the procedure in the law and actual practice. In outlining these differences, the report shall identify procedural inefficiencies, bottlenecks and potential areas for improvement of the procedure. It shall also estimate the approximate costs of these procedures to the parties.